The relationship between life insurance and economic growth - evidence from Kenya (1999 to 2003) - Kanywuiro, Cynthia Wangui (Strathmore University, 2015)
The study assesses the development of the life insurance sector in Kenya, in relation to economic growth. The direction of causality is first established and a comprehensive data analysis is carried out on the relationship between life insurance penetration and GOP growth rate, in the presence of other influencing factors, using a panel of three countries (Kenya, Uganda and Tanzania) within a Generalized Linear Model (GLM) framework. The study comprises a time frame starting from 1999 to 2013. From the model, results indicate no significant relationship between life insurance penetration and economic growth in the presence of other stronger variables. The life expectancy variable in particular shows a significant positive relationship to economic growth; an observation that would prompt further analysis under future research.
Submitted in partial fulfillment of the requirements for the Degree of Bachelor of Business Science in Actuarial Science at Strathmore University
Keywords: Relationship; Life insurance; Economic growth; Kenya; 1999 - 2003